Impact of culvert flooding on carnivore crossings - Craveiro, João (2019)
Along many roads worldwide, drainage culverts are the only structures wildlife can safely use to cross. However, culverts inundate and can become unavailable to terrestrial fauna during rainy periods. We conducted a field study over wet and dry seasons in southern Portugal to assess the effect of culvert flooding on crossings by medium-sized carnivores. We set up track stations inside 30 culverts along intermediate-level traffic roads to evaluate complete crossings (n=1211) and used mixed-effects models to quantify the effects. Carnivores were more likely to cross and crossed more frequently if the culvert had a natural dry pathway at the time of the crossing. Carnivores were also more likely to cross culverts with streams running through them. Moreover, culverts with flowing streams during the wet season were still more likely to be crossed during the dry season when the streams were dry. The significance of the difference in crossing rates between wet and dry seasons was species-specific. Our study reveals that flowing water and dry pathways jointly contribute to promoting crossings by this carnivore community. Culverts including streams may act as a continuation of riparian corridors, being incorporated into carnivores’ movement routes. Our results lend empirical support to recommendations advising the implementation of dry pathways to provide crossing paths. Interventions to offset the transient impacts of water flooding in new or existing culverts can be a cost-effective solution promoting connectivity across roads allowing movement of individuals.